KOMPETENSI PENGADILAN NIAGA DALAM PENYELESAIAN SENGKETA BISNIS DI INDONESIA - Sufiarina Sufiarina (Masalah-Masalah Hukum, 2014)
In the Indonesian justice system found three (3) judicial institutions authorized to settle economic disputes, the District Court, Commercial Court and the Court of Religion. With the presence of the three courts that settle economics disputes, it can also be compared the advantages and disadvantages from each judiciary in the resolution of economic disputes.Assessment implemented through legislation approach as normative legal research which is equipped with study of the principles of law, systematic legal, comparative law, and history of law.This paper find that the settlement of economics disputes through the Commercial Court is superior compared to the other court. Unfortunately, business dispute settlemet authority for the Commercial Court is still limited to bankruptcy issues and delays payment of debt obligations as well as certain disputes in the field of intellectual property rights. Considering the excellence of the Commercial Court in the resolution of economic disputes, it is better to extend the authority of the Commercial Court, including in the areas of tort and breach of contract for other business disputes. Key words: Commercial court, settle economic disputes Dalam sistem peradilan Indonesia ditemukan 3 (tiga) institusi pengadilan yang berwenang menyelesaikan sengketa bisnis, yaitu Pengadilan Negeri, Pengadilan Niaga dan Pengadilan Agama. Dengan terdapatnya tiga lembaga pengadilan yang menyelesaikan sengketa bisnis, maka dapat pula diperbandingan kelebihan dan kekurangan masing-masing lembaga peradilan dalam penyelesaian sengketa bisnis. Pengkajian dilaksanakan melalui pendekatan perundang-undangan sebagai penelitian hukum normatif, dilengkapi dengan penelitian asas-asas hukum, sistematika hukum, dan perbandingan hukum serta sejarah hukum.Tulisan ini memaparkan bahwa penyelesaian sengketa bisnis melalui Pengadilan Niaga lebih unggul dibandingkan dengan pengadilan lainnya, namun kewenangan penyelesaian sengketa bisnis di Pengadilan Niaga saat ini masih terbatas pada masalah kepailitan dan penundaan kewajiban pembayaran utang serta sengketa tertentu di bidang hak kekayaan intelektual. Ada baiknya mengingat keunggulan Pengadilan Niaga dalam penyelesaian sengketa bisnis, kewenangan Pengadilan Niaga dapat diperluas termasuk dalam bidang wanprestasi dan perbuatan melawan hukum bagi sengketa bisnis lainnya.   Kata Kunci: Pengadilan Niaga, Penyelesaian Sengketa Bisnis